Keefektivan Penggunaan Model Pembelajaran Flipped Classroom Berbantuan Media Audio Visual dalam Pembelajaran IPA di Kelas 4 SDN 3 Mekarbakti Garut - Lisnawati Lisnawati (caXra: Jurnal Pendidikan Sekolah Dasar, 2022)
This study aims to test the effectiveness of learning the flipped classroom learning model in grade 4 elementary school with the help of audio-visual media on the form and function of plants. The research method used is quantitative research. Data collection techniques include pre-test and post-test for all students. The t test was conducted to analyze the pre-test and post-test results. From the results of the study it can be concluded that there is an increase in student learning outcomes, which indicates that the online flipped classroom learning model using audio-visual media is effective. In addition, learning like this also adds new experiences for students that are considered effective in learning.